PERANAN PEMBINAAN KEGIATAN EKSTRAKURIKULER PENDIDIKAN AGAMA ISLAM DALAM PENINGKATAN AKHLAK PESERTA DIDIK - Siti Marifa (UNISAN JURNAL, 2024)
This exploration expects to portray the job of training extracurricular exercises for Islamic strict schooling in further developing understudy ethics at MI Amanah Ruteng. To talk about the issues referenced above, information assortment in the field was completed utilizing perception, documentation and interview procedures. The information sources acquired were the Head, Delegate Head, PAI extracurricular movement manager, Head of Organization and understudies. The gathered information was then handled through three phases, in particular information decrease, information show, and information check, then ends were drawn and examined subjectively. The examination results show that 1. PAI extracurricular exercises at MI Amanah Ruteng are fundamentally evolved by adhering to the rules and rules gave by the Division of Religion and the Branch of Public Schooling. Be that as it may, the type of movement is as yet adjusted to the circumstances and conditions of the school and neighborhood. There are 11 types of PAI extracurricular exercises created at MI Amanah Ruteng, in particular week by week love/Friday Tazkir, Al-Qur'an Perusing Learning Project, Tutoring, Tazkir/Recitation, Recognition of Islamic Occasions, Ramadan Exercises (counting Breaking the Quick Together and Ramadhan Pondok ), Kilat Islamic Life experience School, Essential Authority Preparing (LDK), Understudy Imagination Advancement (counting Wall Magazines, Theater, Islamic Groups), Social Help, and Da'wah The travel industry.